Strength and water absorption properties of cement bricks containing sago fine waste - Suraya Hani,; A.W. Norhayati,; I. Ifaniza,; M. Mazizah Ezdianic, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The contamination created by the discharge of sago waste, a by-product of sago milling activities, must be addressed. Using sago waste, specifically sago fine waste (SFW), as a partial cement replacement can be environmentally responsible with a cost-effective choice. The effect of adding sago waste to cement brick characteristics was explored in this study. SFW was utilised to make five brick mixes with partial cement replacement percentages of 0%, 1%, 2%, 3%, 4%, and 5%. The mortar mix has a 1:3 ratio, consistent with Malaysian brick production regulations. All specimens had a water-cement ratio of 0.6 and had been cured for 7, 28, and 56 days for compressive strength tests and density, while water absorption tests were performed on the specimens at cured 28 days. As a result, SFW2 produces the greatest results compared to control bricks, where the compressive strength is 15.8MPa and density is 2157kg/m3 . SFW generally decreased the strength of the brick. However, it was discovered that replacing a maximum of 5% SFW can be used for load-bearing internal wall class 1 because the strength is more than 7 MPa, according to MS 1933: Part 1: 2007. Therefore, This proves the potential of SFW as a new pozzolanic material that can produce more sustainable bricks.